Aplicación de la técnica de espiración lenta prolongada en niños menores de 10 años con infecciones respiratorias agudas del Hospital Pediátrico Alfonso Villagómez, diciembre 2016 - mayo 2017. - Bonifaz Tadayamo, Evelyn Margarita (2017)
Acute respiratory infections are a complex group of diseases caused by various causative agents that affect any point in the airways. The objective of the present study is to eliminate pulmonary secretions more quickly and efficiently through the application of the prolonged slow expiratory exhalation technique (ELPr) in the Pediatric Hospital "Alfonso Villagómez". This technique is performed by placing the child in the supine position on a semi-solid plane, the physiotherapist must exert a joint manual pressure, abdominal and thoracic, at the end of the spontaneous expiratory time in order to help deflation of the lung and thus mobilize pulmonary secretions Accumulated. The study population underwent a treatment plan which was performed once a day for ten days. Each session consisted of 3 sets of 10 repetitions of the prolonged slow exhalation maneuver with breaks between each set of approximately 1-2 minutes. Pulmonary auscultation, saturation, ventilatory pattern, type of expectoration and cough were used as target variables. As a result of this study we observed that the total of the patients according to the geographic location have a 76% that resides in the rural area which implies a greater degree of risk to acquire the acute respiratory infections due to the socioeconomic conditions. Whereas in the initial auscultation we found high frequency crunches with 48% and low frequency crunches of 40%, whereas in the final auscultation we obtained an improvement reaching to cancel the crunches of high and low frequency, obtaining a 92% of the Total population representing normal auscultation. After the completion of the treatment plan, it was observed that the technique used was efficient, demonstrating a highly significant evolution in each of the patients, so we recommend the application of PRR as a first-choice treatment to eliminate bronchial secretions Which occur during acute respiratory infections.